Industrial injuries insurance in Europa and the British Commonwealth before World War II. - Margaret S. Gordon, Industrial injuries insurance in Europe and the British Commonwealth since World War II
Repr.: Occupational Disability and Public Policy. 1963. chapter 7 and 8, p. 191-253.